2014
DOI: 10.2522/ptj.20130499
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Moderate-to-Vigorous Physical Activity and Increased Sedentary Behavior Are Associated With Elevated Blood Pressure Values in Children With Cerebral Palsy

Abstract: Despite the relatively low prevalence of overweight/obesity, a relatively high proportion of children with CP had elevated BP values. Reducing sedentary behavior and increasing habitual physical activity, particularly vigorous activity, should be primary aims of rehabilitation in order to reduce cardiometabolic disease risk in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…38 Thus, considering the highly sedentary lifestyles of most patients with CP, 14,15,39 these current findings provide strong support that this population is at increased risk for accelerated morphologic aging and cardiometabolic abnormalities. Perhaps just as importantly, whereas standard BMI cutoffs are known to have excellent specificity to screen for adiposity in adults with functional or mobility impairments, it lacks the sensitivity to detect excessive adiposity in non-obese persons.…”
Section: Discussionsupporting
confidence: 58%
“…38 Thus, considering the highly sedentary lifestyles of most patients with CP, 14,15,39 these current findings provide strong support that this population is at increased risk for accelerated morphologic aging and cardiometabolic abnormalities. Perhaps just as importantly, whereas standard BMI cutoffs are known to have excellent specificity to screen for adiposity in adults with functional or mobility impairments, it lacks the sensitivity to detect excessive adiposity in non-obese persons.…”
Section: Discussionsupporting
confidence: 58%
“…The prevalence of hypertensive blood pressure values among adults with CP was 20.0% in Ireland, 82 25.5% in the Netherlands, 83 and 30.0% in the USA. 85 Only three studies provided comparative values in the general population; one reported that the prevalence of hypertension was lower among adults with CP 83 and two reported that it was higher. 85 Only three studies provided comparative values in the general population; one reported that the prevalence of hypertension was lower among adults with CP 83 and two reported that it was higher.…”
Section: Metabolic Risk Factorsmentioning
confidence: 99%
“…84 The prevalence of prehypertension and hypertension was 50% among adults with CP in the USA 44 and 10.5% among children with CP in Ireland. 84,85 Four studies reported the prevalence of hyperlipidaemia among adults with CP, but only one compared the prevalence with the general population. 84,85 Four studies reported the prevalence of hyperlipidaemia among adults with CP, but only one compared the prevalence with the general population.…”
Section: Metabolic Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Furthermore, the benefits of walking for obesity prevention and positive effects on the cardiopulmonary system cannot be undervalued. [17][18][19] Finally, the vast majority of parents of young children with developmental disability rate the achievement of walking as the primary goal for their child. 20 When considering these factors, the current delivery of weekly PT services should be amended by innovative, parent-friendly, ancillary, evidence-based programs that can provide a more appropriate dosage of walking training during critical developmental stages in young children.…”
Section: Introduction and Purposementioning
confidence: 99%